Translation Techniques in Institutional Branding: An Analysis of News Headlines from a Higher Education Institution Website - Ardhan, Dhea Tisane; Arnanda, Rachmat; Khoirunnisa, Ratna (Universitas Pahlawan Tuanku Tambusai, 2025)
The aim of this research is to examine the translation techniques applied in news headlines published on the official website of Vocational Education Program, Universitas Indonesia, and their role in shaping institutional branding. This research applied a qualitative descriptive approach, 58 bilingual headlines (Indonesian–English) were analyzed. The results show a total of 11 translation techniques are found, with literal translation being the most dominant technique applied. By using literal translation, it indicates that the institution wants to brand itself as accurate, credible, and trustworthy institution to international audiences. Furthermore, the findings also suggest that translation techniques in this context goes beyond linguistic transfer, serving as a means to strengthen institutional identity and credibility. By balancing local values with international accessibility, the translations of the news headlines contribute to positioning the institution as both rooted in its cultural background and actively engaged in the global higher education environment.